2020
DOI: 10.1111/1468-0009.12459
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Integrated Care: A Systematic Hermeneutic Review of the Literature on Integrated Care Strategies and Concepts

Abstract: Integrated care is best understood as an emergent set of practices intrinsically shaped by contextual factors, and not as a single intervention to achieve predetermined outcomes. Policies to integrate care that facilitate person‐centered, relationship‐based care can potentially contribute to (but not determine) improved patient experiences. There can be an association between improved patient experiences and system benefits, but these outcomes of integrated care are of different orders and do not necessarily a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
124
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(127 citation statements)
references
References 112 publications
(318 reference statements)
2
124
0
1
Order By: Relevance
“…However, the federal organisation of healthcare leaves considerable room for the implementation of local initiatives, which may need to be considered since large-scale strategies do not always represent the optimal option. 26 Results of the national integrated care survey conducted in 2015–2016 showed that local integrated care initiatives have been steadily growing in Switzerland over the last 20 years and were characterised by a diversity of types and breadth of initiatives, implemented interventions and targeted population, among others. 11 Therefore, the low maturity results according to the SCIROCCO tool probably reflect a limited maturity for integrated care at the federal level rather than the cantonal one.…”
Section: Discussionmentioning
confidence: 99%
“…However, the federal organisation of healthcare leaves considerable room for the implementation of local initiatives, which may need to be considered since large-scale strategies do not always represent the optimal option. 26 Results of the national integrated care survey conducted in 2015–2016 showed that local integrated care initiatives have been steadily growing in Switzerland over the last 20 years and were characterised by a diversity of types and breadth of initiatives, implemented interventions and targeted population, among others. 11 Therefore, the low maturity results according to the SCIROCCO tool probably reflect a limited maturity for integrated care at the federal level rather than the cantonal one.…”
Section: Discussionmentioning
confidence: 99%
“…While it may be tempting to look for the entrepreneurial health systems that disrupted care approaches and have high care quality outcomes and expect other systems to be able to follow those models, it has been noted that those efforts may be effective in making systems look more similar, but not actually bring about improvements in efficiency or outcomes when changes are implemented without consideration of each system's unique characteristics and context. 45,46 While labels such as "redesigning" or "transforming" care have intuitive appeal and many health care stakeholders recognize there are numerous opportunities for improving processes that should lead to better outcomes, we are still a long way from being able to systematically measure these changes. System uses quality and analytic teams, IT, and providers to develop care strategies using evidencebased guidelines and standard order sets (in EHR); builds tools for measurement and assessment.…”
Section: Discussionmentioning
confidence: 99%
“…The tension between the need for models and the strategic selection and adaptation of models to fit local needs points to the importance of informed and skilled health system leaders. While it may be tempting to look for the entrepreneurial health systems that disrupted care approaches and have high care quality outcomes and expect other systems to be able to follow those models, it has been noted that those efforts may be effective in making systems look more similar, but not actually bring about improvements in efficiency or outcomes when changes are implemented without consideration of each system's unique characteristics and context 45,46 …”
Section: Discussionmentioning
confidence: 99%
“…Whilst previous reviews have been conducted, these have mainly been limited to searches of the published literature, which may not adequately capture efforts in private or voluntary sector care organisations, where most social care is provided. [9,10,11,12] Moreover, few earlier studies have speci cally examined the literature related to England in order to consider the contextual factors of this setting. There is also a relative paucity of evidence that considers integration in relation to primary care, where most care of older adults with multimorbidity occurs.…”
Section: Introductionmentioning
confidence: 99%